Is there a Relation between Chlamydia Infection and Primary Biliary Cirrhosis? - Patrick S. C. Leung; Ogyi Park; Shuji Matsumura; Aftab A. Ansari; Ross L. Coppel; M. Eric Gershwin (Clinical and Developmental Immunology)
Over the past two decades, a number of studies have failed to provide direct evidence of specific microbial chronic infection in primary biliary cirrhosis (PBC). However, a recent report suggests that there is a specific association of Chlamydia pneumoniae in patients with PBC and that C. pneumoniae or similar antigens might play a role in the pathogenesis of disease. To determine if Chlamydia infection is associated with PBC, we applied a combination of immunological and molecular approaches to investigate (a) the serological reactivity against two common Chlamydia human pathogens, C. pneumoniae and C. trachomatis, by immunoblotting, (b) the presence of Chlamydia in liver samples of patients with PBC and controls by PCR amplification of Chlamydia specific 16S rRNA and (c) the presence of Chlamydia proteins in liver samples of patients with PBC and controls by immunohistochemical staining. By immunoblotting, C. trachomatis and C. pneumoniae specific serological antibodies were found in 52/57 (91.2%) AMA positive PBC, 7/33 (21/2%) of AMA negative PBC, 1/25 (4%) PSC, 0/15 (0%) Sjorgen's syndrome and 0/20 (0%) systemic lupus erythematosus patients and 0/20 (0%) healthy volunteers at 1:200 sera dilution. PBC sera reacted to Chlamydia and E. coli lysates in western blots up to a maximum of 10-4 dilution. However, PCR amplification of the Chlamydia specific 16S rRNA gene was negative in 25/25 PBC livers but positive in 1/4 PSC liver, 3/6 in other liver disease controls and 1/4 normal liver samples. While two commercially available specific monoclonal antibodies stained positive controls (Chlamydia infected HEp-2 cells) they failed to detect Chlamydia antigens in PBC livers. The detection of Chlamydia specific antibodies but not Chlamydia rRNA gene and Chlamydia antigens in PBC suggests that Chlamydia infection is not involved in PBC.